Implementation of the Numbered Heads Together Model to Enhance Students’ Critical Thinking Skills in Social Studies - Erni; Tetep; Lili Dianah (Universitas Negeri Yogyakarta, 2026)
This study aims to describe the implementation of the Numbered Heads Together (NHT) learning model in Social Studies (IPS) and to examine the development of students’ critical thinking skills. This research employed a qualitative approach with a descriptive method. The subjects were students of class VIII B at SMPN 3 Tarogong Kidul. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results indicate that the implementation of the NHT model improves student engagement in learning, as evidenced by increased participation in discussions, confidence in expressing opinions, and social interaction among students. Furthermore, students’ critical thinking skills show significant development, particularly in analysis, explanation, and inference. Students are able to identify problems, connect information, provide logical arguments, and draw systematic conclusions. However, evaluation skills remain less developed and require more intensive practice. Thus, the Numbered Heads Together (NHT) learning model is effective in enhancing student engagement and gradually developing critical thinking skills in Social Studies learning.